Honing English as a foreign language learners’ language abilities through critical pedagogy - Farangi, Mohamadreza; Ghodrat, Nazanin (International Journal of Education and Cognitive Sciences, 2022)
Critical pedagogy, by all means, is an attitude which serves the world through the word (Freire 1970) and leads to self-worth. Students in a critical pedagogical language classroom learn not only how to deal with studying and learning what is meaningful to their life, but also how to know and overcome their deficiencies and lacks which eventually brings on self-esteem. This paper works out to feature in how critical pedagogy consolidates students’ language learning. For this reason, two sets of instruments including a language proficiency test (Cambridge 2005) among 90 participants and a teacher-made language proficiency test as pre-test and posttest among 40 were administered. The findings through t-test acutely demonstrated that the mean performances of language proficiency (0.016) in experimental group was higher than the control group and expresses significant difference (P ≤ 0.05). This showed that the incorporation of the critical pedagogy into the language classroom can benefit EFL learners.